Filling the gap in distribution ranges and conservation status in Ctenomys (Rodentia: Ctenomyidae) - Caraballo, Diego Alfredo (2023)
South American subterranean rodents of the genus Ctenomys (Rodentia, Ctenomyidae, tuco-tuco) are one of the most diverse genera among mammals. Recently described species, new taxonomic revisions, and new distribution range delimitation made the revision of distribution areas and conservation status of these mammals mandatory. Implementing the first part of the DAMA protocol (document, assess, monitor, act), here we compile updated sets of species distribution range maps and use these and the number of collection localities to assess the conservation status of ctenomyids. We integrate potential for conservation in protected areas, and levels of habitat transformation to revise previous conservation status assessments and propose the first assessment for all Data Deficient or not evaluated species of tuco-tucos. Our results indicate that 53 (78%) of these species are threatened and that 47 (69%) have little or no overlap with protected areas, emphasizing the urgent need to conduct conservation efforts. Here, 18 of 22 species previously classified as Data Deficient resulted in them being put in an at-risk category (VU, EN, CR). In addition, nine species that have not been previously evaluated were classified as threatened, with these two groups comprising more than 47% of the known species. These results posit that the Ctenomyidae are the rodent family with the greatest number of species at risk of extinction. Finally, a total of 33 (49%) species have been reported from three or fewer localities; all considered threatened through the approach implemented in this study. These geographically restricted taxa should be given more attention in conservation programs since the richness of this genus relies on the survival of such species.